Treatment Of Acid Mine Drainage Using Fly Ash, Bottom Ash, And Lime Mixed - Fadhilah Fadhilah; Faiz Ramadhan; Rusli HAR (STKIP Singkawang, 2022)
Coal mining will form acid mine drainage in former open pit mines. If acid mine water enters community waters, it will cause disturbance to biota and decrease water quality. Sawahlunto is one of the cities in Indonesia that has a coal mining area located near a settlement. With the acid mine drainage, if it rains, the water will flow into the river where the water is used by the community. Part of the coal is used as fuel for the Sijantang Sawahlunto PLTU. The fuel also produces waste in the form of combustion ash known as fly ash and bottom ash (FABA). This study uses FABA to neutralize acid mine water to meet the community's irrigation water needs. This research will determine the appropriate mass of FABA in neutralizing acid mine drainage. Acid mine water comes from the former mining pit of PT. High Guguak Coal with a pH of 2.88. Then the acid sample is brought to the laboratory to be mixed with FABA and lime. 4.98 grams of FABA with 0.02 lime can neutralize 200 mL of acid mine drainage and change the pH from 2.88 to 7.91. FABA can be included in the settling pond to neutralize acidic water before it is released into community waters.